2022
DOI: 10.18621/eurj.970465
|View full text |Cite
|
Sign up to set email alerts
|

Use of del Nido cardioplegia in adult cardiac surgery

Abstract: In most adult cardiac surgery operations, the heart must be completely immobile and isolated from the blood. Therefore, the heart is stopped in diastole and a still operative site is obtained. Cardiac arrest results in ischemiareperfusion injury. For these reasons, myocardial protection and the prevention of damages are required. Various cardioplegia solutions are used for this purpose. It can be said that cardioplegia is the gold standard method of myocardial protection in cardiac arrest. Nowadays, "Single-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The solution's efficacy and safety make it a promising option for cardiac surgery in both adult and pediatric populations (7,8). Del Nido cardioplegia has also been proven effective in adult minimal invasive cardiac surgeries and acquired cases (coronary artery bypass, valvular, and combined surgeries) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution's efficacy and safety make it a promising option for cardiac surgery in both adult and pediatric populations (7,8). Del Nido cardioplegia has also been proven effective in adult minimal invasive cardiac surgeries and acquired cases (coronary artery bypass, valvular, and combined surgeries) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…CPB time and total operation time were significantly shorter in the del Nido group. Additionally, Amac et al(9) conducted a review of articles regarding the use of single-dose Bretschneider cardioplegia and single-dose del Nido cardioplegia in adult cardiac surgery. Their findings showed that del Nido cardioplegia was a superior and safer technique for myocardial protection, resulting in reduced aortic cross-clamp duration, cardiopulmonary bypass time, and required cardioplegia solution volume.…”
mentioning
confidence: 99%
“…For efficient cardioplegias, it is important to provide rapid diastolic arrest to reduce the consumption of adenosine triphosphate and phosphocreatine by myocytes, and to prevent reperfusion injury [3]. Cardioplegia solutions can be classified as crystalloids or blood cardioplegias according to their composition, and either cold or hot according to the temperature at which they are infused.…”
Section: Introductionmentioning
confidence: 99%
“…Its effectiveness has been demonstrated in many studies in adult cardiac surgery [ 2 , 3 ] . However, the lack of a standard preparation, the high potassium content, and the risks of lidocaine toxicity in repeated doses are its disadvantages [ 4 ] . Custodiol® is used in complex cardiac surgery and transplant surgery in many centers with a single dose.…”
mentioning
confidence: 99%